2020
DOI: 10.2188/jea.je20190091
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes and Mortality From Respiratory Diseases: The Japan Collaborative Cohort Study

Abstract: Background: Little evidence is available about the association between diabetes and respiratory disease mortality among Japanese populations. We aimed to explore the association between diabetes and the risk of respiratory diseases mortality through a nationwide prospective study in Japan. Methods: We followed 95,056 participants (39,925 men and 55,131 women) for a median 17.1 years. The information about diabetes status, sociodemographic characteristics, and lifestyles was collected at baseline. Cox proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…Although men outnumbered women in the diabetes population, we uncovered women as a risk factor for CRD among patients with diabetes, consistent with previous research findings (14,17,22). Men were more affected by severe community-acquired pneumonia (31) due to a higher proportion of smokers (32).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Although men outnumbered women in the diabetes population, we uncovered women as a risk factor for CRD among patients with diabetes, consistent with previous research findings (14,17,22). Men were more affected by severe community-acquired pneumonia (31) due to a higher proportion of smokers (32).…”
Section: Discussionsupporting
confidence: 89%
“…Our finding showed that 18.95%-20.53% of diabetes patients suffered CRD, which is higher than the overall population prevalence (25). In general, diabetes patients have a significant association with the risk of death from CRD, particularly from respiratory infection (17). Similar studies (18,(26)(27)(28)(29) conducted in different areas also confirmed the link between diabetes and higher risk prevalence and mortality from CRD such as TB, COPD, and obstructive sleep apnea, among others.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Metabolism-induced oxidative stress may promote epithelial mesenchymal transformation, leading to the accumulation of tumor genes and tumor suppressor gene mutations, promoting gastric mucosal damage and interfering with repair [13]. Furthermore, hyperglycemia can generate more energy through glycolysis and lactic acid pathways, leading to energy balance imbalance, affecting intracellular metabolism and damaging immune function, complement activation, and antioxidant systems [57]. Patients with DM may have increased susceptibility to H. pylori infection and delayed wound healing after infection due to immunosuppression caused by hyperglycemia [58].…”
Section: Effects Of Hyperglycemia and Hyperinsulinemia On Dm And Gcmentioning
confidence: 99%